2022
DOI: 10.3389/fpsyg.2022.816128
|View full text |Cite
|
Sign up to set email alerts
|

School Belonging and Reading Literacy: A Multilevel Moderated Mediation Model

Abstract: School belonging is of great significance to students' physical and mental health development, especially academic improvement. However, the mechanism of the influence of school belonging on student academic achievement should be further explored, especially reading performance. Based on ecological systems theory and self-determination theory, the present research constructs a multilevel design to examine a moderated mediation model in which school belonging as a level-1 predictor, mastery goal orientation as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 66 publications
(159 reference statements)
0
7
0
1
Order By: Relevance
“…School belonging has been seen as an important factor in academic performance. Some studies focused on the direct impact of students' school belonging on their academic performance (Korpershoek et al, 2020;Tan et al, 2022), and other research has further explored the mediating role of school belonging on the relationships between family and school factors and students' academic performance. Studies on the mediating role of school belonging have shown that parent involvement can influence the academic performance of middle and high school students (Kuperminc et al, 2007), that peer cooperation can influence academic performance of American middle school students (Knifsend et al, 2018), and that school climate can influence academic performance among Chinese middle school students (Huang, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…School belonging has been seen as an important factor in academic performance. Some studies focused on the direct impact of students' school belonging on their academic performance (Korpershoek et al, 2020;Tan et al, 2022), and other research has further explored the mediating role of school belonging on the relationships between family and school factors and students' academic performance. Studies on the mediating role of school belonging have shown that parent involvement can influence the academic performance of middle and high school students (Kuperminc et al, 2007), that peer cooperation can influence academic performance of American middle school students (Knifsend et al, 2018), and that school climate can influence academic performance among Chinese middle school students (Huang, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Although it would have been ideal to have had identical scales across measurement points, both operationalizations of the construct used items employed in multiple prior studies (Goodenow, 1993; Korpershoek et al, 2020; Voelkl, 1996). The items from the PISA survey have been used widely in research on students in lower-secondary school (Chiu et al, 2016; Cueto et al, 2010; Godor & Szymanski, 2017; OECD, 2003, 2017; Tan et al, 2022), whereas items similar to those used in the TREE survey have been used repeatedly in research on students in upper-secondary school (Demanet & Van Houtte, 2012; D’hondt et al, 2015; Holt & Espelage, 2003; see also Galliher et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Asessmen merupakan kegiatan untuk mengungkapkan kualitas proses dan hasil pembelajaran . Prestasi akademik merupakan indikator penting untuk mengevaluasi status dan kualitas belajar siswa dari pendidikan sekolah (Tan et al, 2022) .Siswa yang akan mengikuti ANBK merupakan siswa seleksi pemerintah melalui online. ANBK memiliki penilaian tiga level dengan masing-masing kategori adalah Perlu Intervensi Khusus, Dasar, dan Cakap/Mahir.…”
Section: Pendahuluanunclassified